In-Hospital Cardiac Complications after Intracerebral Hemorrhage. Issue 6 (August 2014) - Putaala, J.; Lehto, M.; Meretoja, A.; Silvennoinen, K.; Curtze, S.; Kääriäinen, J.; Koivunen, R.-J.; Kaste, M.; Tatlisumak, T.; Strbian, D.
Background and purpose: Data on cardiac complications and their precipitants after intracerebral hemorrhage are scarce. We examined the frequency and risk factors for serious in-hospital cardiac events in a large cohort of consecutive intracerebral hemorrhage patients. Methods: A retrospective chart review of 1013 consecutive patients with nontraumatic intracerebral hemorrhage treated at the Helsinki University Central Hospital (2005–2010). We excluded patients with intraparenchymal hematoma related to sub-arachnoid hemorrhage or intracerebral hemorrhage because of fibrinolytic therapies for acute ischemic stroke or myocardial infarction. Serious in-hospital cardiac event was defined as any of in-hospital poststroke acute myocardial infarction, ventricular fibrillation or tachycardia, moderate to serious acute heart failure, or cardiac death. Results: Among the 948 patients included, ≥1 serious in-hospital cardiac event occurred in 39 (4·1%) patients after a median delay of two-days from stroke onset (acute myocardial infarction in three patients, ventricular fibrillation or tachycardia in three patients, acute heart failure in 36 patients, and cardiac death in three patients). Hospital stay was longer in patients with serious in-hospital cardiac event than in those without (median 12, interquartile range 7–19 vs. 8, 3–14; P = 0·001), with no difference in in-hospital mortality (23·1% vs. 24·3%; P = 0·86). In multivariable logistic regression analysis adjusted for age, gender, and diabetes, atrial fibrillation during hospitalization (odds ratio 6·68 for new-onset atrial fibrillation, 95% confidence interval 2·11–21·18; 4·46 for old atrial fibrillation, 2·08–9·56), and history of myocardial infarction (3·20, 1·18–8·66) were independently associated with serious in-hospital cardiac events. Conclusions: After intracerebral hemorrhage, 4% of patients suffer an acute serious cardiac complication. Those with history of myocardial infarction or in-hospital atrial fibrillation are at greater risk for such events.